Kepemimpinan Transformasional di Sekolah: Analisis Bibliometrik Database Scopus - Taufiq, Muhammad; Satori, Djaman; Sururi, Sururi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: This study presents a bibliometric analysis of research on transformational leadership in schools using data from the Scopus database between 2014 and 2024. Using VOSviewer and R Studio Biblioshiny for analysis, we examined publication trends, influential contributors, and research themes within this field. The findings revealed significant growth in publications, with an annual increase of 16.65%, indicating increasing scientific interest, especially during the COVID-19 pandemic. Influential contributions were identified through the most cited documents and a three-field plot, which highlighted lead authors, countries such as Indonesia and Malaysia, and leading journals such as the Journal of Educational Administration. Keyword co-occurrence analysis revealed six thematic clusters, including school leadership, teacher performance, organizational outcomes and innovation, demonstrating the multidimensional nature of the field. This analysis provides valuable insights into the global research landscape on transformational leadership in education, emphasizing its critical role in addressing contemporary educational challenges and informing future research directions. Keywords: Bibliometrics, School, scopus, transformational leadership. Abstrak: Studi ini menyajikan analisis penelitian bibliometrik tentang kepemimpinan transformasional di sekolah menggunakan data dari database Scopus antara tahun 2014 dan 2024. Dengan menggunakan VOSviewer dan R Studio Biblioshiny untuk analisis, kami memeriksa tren publikasi, kontributor pengaruh, dan tema penelitian dalam bidang ini. Temuan ini menunjukkan adanya pertumbuhan publikasi yang signifikan, dengan peningkatan tahunan sebesar 16,65%, yang menunjukkan meningkatnya minat ilmiah, terutama selama pandemi COVID-19. Kontribusi yang berpengaruh diindentifikasi melalui dokumen yang paling banyak dikutip dan plot tiga bidang, yang menyoroti penulis utama, negara-negara seperti Indonesia dan Malaysia, dan jurnal terkemuka seperti Journal of Educational Administration. Analisis kejadian bersama kata kunci mengungkap enam kelompok tematik, termasuk kepemimpinan sekolah, kinerja guru, hasil organisasi, dan inovasi, yang menunjukkan sifat multidimensi dari bidang ini. Analisis ini memberikan wawasan berharga mengenai lanskap penelitian global mengenai kepemimpinan transformasional dalam pendidikan, menekankan peran penting kepemimpinan transformasional dalam mengatasi tantangan pendidikan kontemporer dan memberikan informasi arah penelitian di masa depan. Kata kunci: Bibliometrik, kepemimpinan transformasional, Scopus, sekolah